(3QSGdI aj af GdJLhjOs - (3gGOj Hf YHGS Hf Ydj GHf cGTa GdZWGA, J (B1360(3g`s ((3GHf GdYHGS Hf Ydj Hf LYaQ GdfLajs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3hHYO agPg QSGdI JJYdb HGdJLhjO efJNHI ef GdcJH GdeHShWI(B...s
(3BNQgG (B:s
(3adPdc UGQ GdGYJfGA HTCf GdbQBf GdeLjO(B... (3dFdG jchf ef GdCNSQjf CYeGdG GdPjf Vd SYjge aj GdMjGI GdOfjG(B... (3CjbXfG Gddg hZjGce ef fheI GdZGadjf hUdi Gddg Ydi eMeO hBdg GdWGgQjf(B.(3JeJ GdQSGdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B8(3, U(B58s
(3eYLe GdeDdajf(B: (3L(B4(3, U(B47s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs